2008
DOI: 10.1130/ges00117.1
|View full text |Cite
|
Sign up to set email alerts
|

A prominent geophysical feature along the northern Nevada rift and its geologic implications, north-central Nevada

Abstract: We consider the origin and character of a prominent large-scale geophysical feature in north-central Nevada that is coincident with the western margin of the northern Nevada rift-a mid-Miocene rift that includes mafi c dike swarms and associated volcanic rocks expressed by a NNW-striking magnetic anomaly. The geophysical feature also correlates with mid-Miocene epithermal gold deposits and is coincident with the central part of the Battle Mountain-Eureka mineral trend. The Reese River Valley, a 2-km-deep Cenoz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Previous workers have suggested that the location and trend of the NNR may have been controlled by an existing crustal structure (e.g., Theodore et al, 1998;John et al, 2000;Ponce and Glen, 2008). This structure has been interpreted as a near-vertical crustal-scale fault parallel and adjacent to the NNR based on resistivity (Grauch et al, 2003) and gravity data (Ponce and Glen, 2008).…”
Section: Orientation Of the Northern Nevada Riftmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous workers have suggested that the location and trend of the NNR may have been controlled by an existing crustal structure (e.g., Theodore et al, 1998;John et al, 2000;Ponce and Glen, 2008). This structure has been interpreted as a near-vertical crustal-scale fault parallel and adjacent to the NNR based on resistivity (Grauch et al, 2003) and gravity data (Ponce and Glen, 2008).…”
Section: Orientation Of the Northern Nevada Riftmentioning
confidence: 96%
“…This structure has been interpreted as a near-vertical crustal-scale fault parallel and adjacent to the NNR based on resistivity (Grauch et al, 2003) and gravity data (Ponce and Glen, 2008). In the right circumstances, dikes can propagate along fractures that are not perpendicular to the least principal stress (e.g., Delaney et al, 1986), but NNR dikes do not appear to intrude preexisting faults where exposed in the fi eld and it is diffi cult to argue they record anything other than the least principal stress in the central part of the area shown in Figure 2 from ca.…”
Section: Orientation Of the Northern Nevada Riftmentioning
confidence: 99%
“…There is a pronounced gravity gradient, increasing from west to east, at the western edge of the rift. This steep gradient is visible on all profi les to the south, except profi le EE', and likely refl ects the juxtaposition of dense basement rocks east of the eastern north-ern Nevada rift, with less dense basin deposits and basement rocks west of the rift (Ponce and Glen, 2008). In profi le EE', the gravity gradient is less pronounced because the eastern northern Nevada rift is juxtaposed against dense Paleozoic rocks on the west in the Shoshone Range, which decreases the density contrast.…”
Section: Profi Le Aa'mentioning
confidence: 96%
“…Glen and Ponce (2002) describe several large-scale, NNW-trending, arcuate, mid-Miocene crustal structures in northern Nevada, including the eastern northern Nevada rift, which passes just west of the Beowawe geothermal system and is the focus of this study. The eastern northern Nevada rift has been divided into multiple segments from north to south based on interpretationof magnetic data (Zoback et al, 1994;Ponce and Glen, 2008). Zoback and Thompson (1978) and Glen and Ponce (2002) speculate the eastern northern Nevada rift and other associated rifts were localized along regional crustal fractures that were reactivated during emergence of the Yellowstone hotspot along the Oregon-Idaho border.…”
Section: Regional and Local Geology And Resourcesmentioning
confidence: 99%
See 1 more Smart Citation